Fast two‐dimensional grid and transmission X‐ray microscopy scanning methods for visualizing and characterizing protein crystals. Issue 3 (16th May 2016) - Wojdyla, Justyna Aleksandra; Panepucci, Ezequiel; Martiel, Isabelle; Ebner, Simon; Huang, Chia-Ying; Caffrey, Martin; Bunk, Oliver; Wang, Meitian
Abstract : This article reports the incorporation of a fast continuous grid scan with both still and oscillation images into the Swiss Light Source macromolecular crystallography beamlines and its application in visualization of protein crystals with scanning transmission X‐ray microscopy. Abstract : A fast continuous grid scan protocol has been incorporated into the Swiss Light Source (SLS) data acquisition and analysis software suite on the macromolecular crystallography (MX) beamlines. Its combination with fast readout single‐photon counting hybrid pixel array detectors (PILATUS and EIGER) allows for diffraction‐based identification of crystal diffraction hotspots and the location and centering of membrane protein microcrystals in the lipid cubic phase (LCP) in in meso in situ serial crystallography plates and silicon nitride supports. Diffraction‐based continuous grid scans with both still and oscillation images are supported. Examples that include a grid scan of a large (50 nl) LCP bolus and analysis of the resulting diffraction images are presented. Scanning transmission X‐ray microscopy (STXM) complements and benefits from fast grid scanning. STXM has been demonstrated at the SLS beamline X06SA for near‐zero‐dose detection of protein crystals mounted on different types of sample supports at room and cryogenic temperatures. Flash‐cooled crystals in nylon loops were successfully identified in differential and integrated phase images. Crystals of just 10 µm thickness were visible in integrated phase images using data collected with the EIGER detector. STXM offers a truly low‐dose method for locating crystals on solid supports prior to diffraction data collection at both synchrotron microfocusing and free‐electron laser X‐ray facilities.